Eating disorders associated with weight-loss processes in Spanish highperformance women's Olympic wrestling athletes. A qualitative study - Flores, M. R.; Mon López, D.; Angosto, S.; López-Gullón, J. M. (International Journal of Wrestling Science, 2022)
OBJECTIVE: The aim of this study is to qualitatively analyse the eating behaviours and possible eating disorders associated with weight-loss processes in Spanish high-performance women's Olympic wrestling athletes.